Receptor-Mediated Endocytosis and Brain Delivery of Therapeutic Biologics - Guangqing Xiao; Liang-Shang Gan (International Journal of Cell Biology)
Transport of macromolecules across the blood-brain-barrier (BBB) requires both specific and nonspecific interactions between macromolecules and proteins/receptors expressed on the luminal and/or the abluminal surfaces of the brain capillary endothelial cells. Endocytosis and transcytosis play important roles in the distribution of macromolecules. Due to the tight junction of BBB, brain delivery of traditional therapeutic proteins with large molecular weight is generally not possible. There are multiple pathways through which macromolecules can be taken up into cells through both specific and nonspecific interactions with proteins/receptors on the cell surface. This review is focused on the current knowledge of receptor-mediated endocytosis/transcytosis and brain delivery using the Angiopep-2-conjugated system and the molecular Trojan horses. In addition, the role of neonatal Fc receptor (FcRn) in regulating the efflux of Immunoglobulin G (IgG) from brain to blood, and approaches to improve the pharmacokinetics of therapeutic biologics by generating Fc fusion proteins, and increasing the pH dependent binding affinity between Fc and FcRn, are discussed.